COVID-19 and the Experiences and Needs of Staff and Management Working at the Front Lines of Long-Term Care in Central Canada. Issue 4 (9th December 2022) - Reynolds, Kristin; Ceccarelli, Laura; Pankratz, Lily; Snider, Tara; Tindall, Cameron; Omolola, Daniel; Feniuk, Chelsea; Turenne-Maynard, Julie
Abstract: Across the globe, long-term care has been under increased pressure throughout the COVID-19 pandemic. This is the first study to examine the experiences and needs of long-term care staff and management during COVID-19, in the Canadian context. Our group conducted online survey research with 70 staff and management working at public long-term care facilities in central Canada, using validated quantitative measures to examine perceived stress and caregiver burden; and open-ended items to explore stressors, ways of coping, and barriers to accessing mental health supports. Findings indicate moderate levels of stress and caregiver burden, and highlight the significant stressors associated with working in long-term care during the COVID-19 pandemic (i.e., rapid changes in pandemic guidelines, increased workload, "meeting the needs of residents and families", fear of contracting COVID-19 and COVID-19 coming into long-term care facilities, and concern over a negative public view of long-term care staff and facilities). A small subset (13.2%) of our sample identified accessing mental health supports to cope with work-related stress, with most participants identifying barriers to seeking help. Novel findings of this research highlight the significant and unmet needs of this high-risk segment of the population.